Estimation of diffusion behaviour of metals used for the creation of multilayered contacts to heterostructures based on GaAs - V. V. Arbenina; A. S. Kashuba; E. V. Permikina (Тонкие химические технологии, 2014)
The formation of the microstructure of metallization layers was investigated, and the calculations of the size of diffusion areas on the interphase boundaries in systems metal (Au, Ti, Pt)/GaAs and metal / metal was executed. The formation of the microstructure is accompanied by development in layers of internal stress. Internal stress in many respects determines the electrical and mechanical characteristics of the metallization layers and the influence of diffusion processes on the rate. Using the obtained results it is possible to choose purposefully the modes of drawing of metal layers and annealing structures in order to obtain systems of metallization with small internal stress and high level conductivity.